Association between intraoperative fluid management and postoperative outcomes in living kidney donors: a retrospective cohort study - Ja Eun Lee; Chisong Chung; Sunghae Park; Kyo Won Lee; Gaab Soo Kim (Scientific Reports)
Abstract Optimal fluid strategy for laparoscopic donor nephrectomy (LDN) remains unclear. LDN has been a domain for liberal fluid management to ensure graft perfusion, but this can result in adverse outcomes due to fluid overload. We compared postoperative outcome of living kidney donors according to the intraoperative fluid management. Five hundred and five LDNs performed over a six-year period at a tertiary hospital were analyzed. Donors were divided into tertiles according to intraoperative crystalloid infusion rate (ml/kg/hr), and associations between the tertile and outcomes were investigated with inverse probability of treatment weighting with entropy balancing. Primary outcome was maximal rise of serum creatinine (sCr). Secondary outcomes were sCr rise meeting Acute Kidney Injury (AKI) criteria, time to reach minimal sCr, and length of hospital stay. The following covariates were used: age, sex, body weight, height, diabetes mellitus, hypertension, preoperative estimated glomerular filtration rate, operation duration, surgeon, nephrectomy side, and estimated blood loss. Median intraoperative crystalloid infusion rate was 3.5, 4.6, and 6.0 ml/kg/hr in the first, second, and third tertile, respectively (group 1, 2, and 3). Maximal rise of sCr did not differ between groups (P = 0.274). Twofold increase in sCr (equivalent to stage 2 AKI) during the first week and prolonged hospitalization were most frequent in group 1 [7.8 vs. 1.1 vs. 1.5%, P = 0.004; 7.9 vs. 3.1 vs. 0.7%, P = 0.003]. Time to reach minimal sCr was longest in group 1. No differences were found in recipient early renal function. Hypovolemia is associated with poor postoperative outcomes after LDN. Efforts to find the optimal fluid management should be continued.